Evaluation of viability, developmental competence, and apoptosis-related transcripts during in vivo post-ovulatory oocyte aging in zebrafish Danio rerio (Hamilton, 1822) - Konar, Essaikiammal Sodalai Muthu; Mai, Knut; Brachs, Sebastian; Waghmare, Swapnil Gorakh; Samarin, Azadeh Mohagheghi; Policar, Tomas; Samarin, Azin Mohagheghi (Frontiers in Veterinary Science, 2024)
Introduction Post-ovulatory aging is a time-dependent deterioration of ovulated oocytes and a major limiting factor reducing the fitness of offspring. This process may lead to the activation of cell death pathways like apoptosis in oocytes. Methodology We evaluated oocyte membrane integrity, egg developmental competency, and mRNA abundance of apoptosis-related genes by RT-qPCR. Oocytes from zebrafish Danio rerio were retained in vivo at 28.5°C for 24 h post-ovulation (HPO). Viability was assessed using trypan blue (TB) staining. The consequences of in vivo oocyte aging on the developmental competence of progeny were determined by the embryo survival at 24 h post fertilization, hatching, and larval malformation rates. Results The fertilization, oocyte viability, and hatching rates were 91, 97, and 65% at 0 HPO and dropped to 62, 90, and 22% at 4 HPO, respectively. The fertilizing ability was reduced to 2% at 8 HPO, while 72% of oocytes had still intact plasma membranes. Among the apoptotic genes bcl-2 (b-cell lymphoma 2), bada (bcl2-associated agonist of cell death a), cathepsin D, cathepsin Z, caspase 6a, caspase 7, caspase 8, caspase 9, apaf1, tp53 (tumor protein p53), cdk1 (cyclin-dependent kinase 1) studied, mRNA abundance of anti-apoptotic bcl-2 decreased and pro-apoptotic cathepsin D increased at 24 HPO. Furthermore, tp53 and cdk1 mRNA transcripts decreased at 24 HPO compared to 0 HPO. Discussion Thus, TB staining did not detect the loss of oocyte competency if caused by aging. TB staining, however, could be used as a simple and rapid method to evaluate the quality of zebrafish oocytes before fertilization. Taken together, our results indicate the activation of cell death pathways in the advanced stages of oocyte aging in zebrafish.